Evaluasi Capaian KKM Mata Pelajaran Matematika SD dan SMP melalui Penerapan Cooperative Learnig Tipe Stad: Studi Meta-Analisis - Samritin Samritin (Departement of Mathematics Education, 2020)
The success of learning is one of the indicators seen from the cut score achievements. Learning is said to be successful if it can lead students to reach or exceed the cut score that has been set. The use of learning methods leads students to achieve the cut score if the method matches the material and student characteristics. In mathematics, the cooperative learning type STAD is often used as alternative learning for this purpose. Much has been done to improve mathematics learning outcomes by applying STAD at the elementary and junior high school levels. This study examines the results of classroom action research (CAR) publications in mathematics involving nine (9) publications as a sample. Research data is collected online through the Publish or Parish application and indexed in the Google Scholar database. Data analysis was performed using Excel and JASP programs. Based on the results of the analysis, it was found that the SE publications studied were homogeneous, both cycle I and cycle II. The results of data analysis also obtained a summary effect size (SES) of 0.654 and SE of 0.031 in cycle I and an SES of 0.918 with an SE of 0.18 in cycle II. Both SES have a p-value <0.01 which indicates that the SES is significant. The results of the analysis also found that SES belongs to the strong classification. Based on the results of this research analysis concluded that the application of cooperative learning in learning mathematics can improve KKM achievement in learning mathematics at the elementary and junior high school levels. Therefore it is suggested that learning mathematics in class apply the STAD cooperative learning model.